PENGARUH PIJAT OKSITOSIN TERHADAP INVOLUSI UTERUS PADA SUBJEK POSTPARTUM ANEMIA - Armiyanti Armiyanti (Jurnal Ilmiah Kesehatan, 2021)
Purpose: This study aims at analyzing the effects of oxytocin massage on uterine involution to postpartum subjects with anemia. Method: Method of this study is quasi experiment with 36 samples of postpartum mothers with anemia. This study was conducted in November 2017 to January 2018. Samples were taken using random sampling to obtain 18 respondents of intervention group on which oxytocic massage is given, and 18 respondents of control group on which oxytocin massage is not given. The free variables use oxytocin massage, and bound variables are uterine involution. Analysis and effects used in this study is statistical test of Mann-Whitney. Results: The height of uterine fundus on the seventh day in control group is on average of 5.61 cm and 5 cm in intervention group. It is obtained value of p<0,05 in a statistical result, so it can be concluded that there is an average significant difference between uterine involution of intervention group and control group that is started on the fourth day to the seventh day. Conclusion: According to the study result, it can be concluded that oxytocin massage accelerates uterine involution on postpartum subjects with anemia.